Analysis of Leading Sectors Supporting Agriculture through the LQ and Shift Share Approaches in Sumatera - Khoirunnisa, Icha; Ratih, Arivina; Ciptawaty, Ukhti; Wahyudi, Heru; Murwiyati, Asih (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study analyzes the economic impact of agriculture on Sumatra's regional growth from 2018 to 2022, employing quantitative descriptive methods and data from the Provincial Central Statistics Agency (BPS). By utilizing Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share (SS) analyses, the research identifies key agricultural sectors contributing to economic development. Results reveal that plantation crops, forestry, fisheries, and agricultural services are significant contributors, with Riau Province showing the highest relative contribution. Cluster analysis categorizes sectors into four groups, with plantation crops and agricultural services in the second cluster. Sumatera Utara and Riau demonstrate stable economic growth. The study suggests enhancing productivity, expanding export markets, and improving infrastructure and innovation for less significant sectors. Future research should explore non-basis sectors and successful case studies to provide deeper insights into sectoral performance and economic impact.